Agricultural co-operatives for managing natural capital to achieve UN Sustainable Development Goals 12–15: A conceptual framework. Issue 2 (December 2022) - Ghauri, Shahid; Jackson, Elizabeth L.; Marinova, Dora; Mohammadi, Hossein
Abstract: Natural capital is becoming an important topic for global biodiversity and sovereign risk of nations for their food supply chains which can be linked to the United Nations Sustainable Development Goals 12–15. In this paper we explored the literature to develop a conceptual framework to determine how primary industry co-operatives (such as in agriculture and aquaculture) can play a role in managing natural capital. The conceptual framework developed shows that members of co-operatives have roles to act within their organisation that utilise natural capital. Acting out these roles may see the co-operative become pro-active in governing its natural capital based on economic and social goals which are guided by the co-operative principles and values. Working with the financial services sector, co-operatives would be able to engage with their members to educate and share knowledge on strategies to manage and/or mitigate the risk of natural capital depletion. This can be managed through farm management techniques and financial instruments such as credit and insurance. Highlights: Co-operatives can serve as a platform to manage natural capital for agricultural ecosystems. Co-operative members can play an active role engaging with natural capital management. Co-operatives should be considering natural capital as part of its governance. Co-operatives can serve as a facilitator of information, education and knowledge to collectively manage natural capital. Financial services institutions can work with co-operatives to lower their risk to natural capital depletion. Co-operatives can work with financial institutions to provide access to financial services at lower costs.